The silence in her eyes : a novel - Correa, Armando Lucas, 1959-; Caistor, Nick; Williams, Faye (Translator); Molinari, Cecilia (New York : Atria Books, 2024)
"Leah has been living with akinetopsia, or motion blindness, since she was a child. For the last twenty years, she hasn't been able to see movement. As she walks around her upper Manhattan neighborhood with her white stick tapping in front, most people assume she's blind. But the truth is Leah sees a good deal, and with her acute senses of smell and hearing, very little escapes her notice. She has a quiet, orderly life, with little human contact beyond her longtime housekeeper, her doctor, and her elderly neighbor. That all changes when Alice moves into the apartment next door and Leah can immediately smell the anxiety wafting off her. Worse, Leah can't help but hear Alice and a late-night visitor engage in a violent fight. Worried, she befriends her neighbor and discovers that Alice is in the middle of a messy divorce from an abusive husband. Then one night, Leah wakes up to someone in her apartment. She blacks out and in the morning is left wondering if she dreamt the episode. And yet the scent of the intruder follows her everywhere. And when she hears Alice through the wall pleading for her help, Leah makes a decision that will test her courage, her strength, and ultimately her sanity." --
In English, translated from Spanish
Keywords: Vision disorders -- Fiction; Neighbors -- Fiction; Abused wives -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Thrillers (Fiction); Novels